Influence of the air's refractive index on precision angle metrology with autocollimators. (24th May 2018) - Geckeler, Ralf D; Křen, Petr; Just, Andreas; Schumann, Matthias; Krause, Michael
Abstract: In this paper, we discuss a substantial—though previously neglected—error source in precision metrology with autocollimators, specifically, changes in the air's refractive index, with a focus on the dominant impact of pressure changes. Pressure decreases with increasing elevation above sea level and is subject to substantial variation due to weather changes. It causes changes in an autocollimator's angle response which are proportional to the measured angle and which increase linearly with the beam length and air pressure. We characterise this important influence in detail by using extended theoretical and experimental investigations and derive strategies for correcting it. We discuss its implications for the comparison of autocollimator calibrations performed at different metrology institutes which is crucial for validating their calibration capabilities. This work aims at approaching fundamental limits in angle metrology with autocollimators.